2014
DOI: 10.1371/journal.pone.0105504
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Supplementation in Maternal Diet Modulates the Epigenetic Regulation of Hepatic Gluconeogenic Genes in Neonatal Piglets

Abstract: In this study, gestational sows were fed control or betaine-supplemented diets (3 g/kg) throughout the pregnancy, and the newborn piglets were used to elucidate whether maternal dietary betaine affected offspring hepatic gluconeogenic genes through epigenetic mechanisms. Neonatal piglets born to betaine-supplemented sows had significantly higher serum and hepatic betaine contents, together with significantly greater expression of methionine metabolic enzymes in the liver. Interestingly, significantly higher se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…However, we found more enrichment of histone-activated marker H3K4me3 on the LDLR and SR-BI genes’ promoters, which is associated with enhanced gene transcription. It is noted that H3K4me3 is trimethylated by a SAM-dependent enzyme, SETD7 [40], and our previous study has demonstrated that maternal betaine diet increases SETD7 expression in the liver of offspring [41]. Therefore, in the present study, enhanced SAM content may greatly contribute to activate histone modification in the promoters of hepatic cholesterol metabolic genes in the betaine-exposed weaning piglets.…”
Section: Discussionmentioning
confidence: 49%
“…However, we found more enrichment of histone-activated marker H3K4me3 on the LDLR and SR-BI genes’ promoters, which is associated with enhanced gene transcription. It is noted that H3K4me3 is trimethylated by a SAM-dependent enzyme, SETD7 [40], and our previous study has demonstrated that maternal betaine diet increases SETD7 expression in the liver of offspring [41]. Therefore, in the present study, enhanced SAM content may greatly contribute to activate histone modification in the promoters of hepatic cholesterol metabolic genes in the betaine-exposed weaning piglets.…”
Section: Discussionmentioning
confidence: 49%
“…Methylated DNA immunoprecipitation analysis was performed as previously described . Purified genomic DNA from liver tissue was fragmented to a mean size of 300 base pairs (bp).…”
Section: Methodsmentioning
confidence: 99%
“…Betaine is critical for embryonic and fetal development . Maternal betaine supplementation during gestation affects hepatic expression of gluconeogenic and lipogenic genes in neonatal piglets, which involves modifications of DNA methylation on the promoter of affected genes.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic PEPCK1 enzyme activity was detected as previously described (Cai et al, 2014). In brief, 0.5 g of liver tissue was homogenized in a lysis buffer (0.25 M sucrose and 5 mM Tris-HCl, pH 7.4) at 4°C.…”
Section: Milk Compositionmentioning
confidence: 99%